Prosecutorial Discretion, Drug Case Selection, and Inequality in Federal Court. (10th November 2018) - Lynch, Mona
Abstract: In this article, I explore variations in prosecutors' discretionary case selection practices by drawing on findings from a comparative field research project of drug prosecutions conducted in four federal districts. Using data from a series of in-depth interviews with legal actors in each district, I develop a typology of the kinds of drug cases brought in my sample districts, explore the logics underpinning their selection, and examine the potential impact of selection practices on racial inequality in drug caseloads. Findings elucidate the local variations in logics and practices that are nonetheless shaped by broader ideologies and structured incentives that encourage certain types of prosecutions. Prosecutorial discretion at the case selection stage also plays an important role in how cases are adjudicated, which is often closely linked to the logic underpinning the choice to file.